Construction of nanodelivery system based on the interaction mechanism between ultrasound–treated soybean whey protein and quercetin: structure, physicochemical stability and bioaccessibility - Xinru Cao; Jia Cao; Tianhe Xu; Lexi Zheng; Jingyi Dai; Xiaokun Zhang; Tian Tian; Kunyu Ren; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Ultrasonics Sonochemistry)
In this study, soybean whey protein (SWP) nanodelivery system was constructed through ultrasound treatment and quercetin (Que) modification. The effect of ultrasound power on the interaction mode between SWP and Que, and the formation and stability of SWP–Que nanodelivery system were investigated. Optimal ultrasound treatment (300–500 W) produced SWP–Que nanoparticles with smaller particle size, higher ζ–potential values, and more uniform dispersion. Fluorescence spectroscopy and FTIR analyses revealed that SWP primarily binds to Que through hydrophobic interactions. Ultrasound treatment induced the unfolding of the SWP structure, thereby increasing its binding affinity to Que. After 400 W sonication, the encapsulation efficiency can reach 95.63 ± 0.60 %. The SWP–Que nanoparticles protected Que from degradation under environmental stresses (heat, UV, and storage) and improved its bioaccessibility during digestion as the ultrasonic power of 400 W. This study highlights the potential of ultrasound–modified SWP nanoparticles for effective nutrient delivery.